Keeping Kids Safe, Healthy, and Smart - Lebrun, Marcel; Williams, Kimberly (Rowman & Littlefield Publishers, 2009)
Perhaps the most challenging and important role that adults play in society is that of raising children. Every parent and teacher hopes to help children develop into healthy, caring, and intelligent adults. Keeping Kids Safe, Healthy, and Smart is designed for all adults who interact with kids-whether they be parents, teachers, or other caregivers-and provides specific suggestions for keeping children safe from hidden and open dangers wherever they spend time. This book is organized around three different themes of major threats and hidden dangers to children in our country: threats in school spaces (e.g., in classrooms, on buses, on playgrounds, and on sports teams); threats in cyberspace (bullying or harassment and child predators or child pornography), threats in other spaces where children work and play (intrapersonal and interpersonal violence including a wide range of threats such as self-mutilation, accidents, abuse, environmental threats, drugs, and mental illness).